2020
DOI: 10.1186/s13033-020-00372-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementation outcomes of cognitive behavioural therapy delivered by non-specialists for common mental disorders and substance-use disorders in low- and middle-income countries: a systematic review

Abstract: Due to severe shortages of specialist mental health personnel in low-and middle-income countries (LMICs), psychological therapies are increasingly being delivered by non-specialist health workers (NSHWs). Previous reviews have investigated the effectiveness of NSHW-delivered psychological therapies, including cognitive behavioural therapy (CBT), in LMIC settings. This systematic review aims to synthesise findings on the implementation outcomes of NSHW-delivered CBT interventions addressing common mental disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
(209 reference statements)
1
28
0
4
Order By: Relevance
“…We found several similarities when comparing our results to previous systematic reviews on implementation outcomes. Similar to previous reviews on implementation outcomes in LMICs, acceptability, appropriateness, and feasibility were the most frequently reported implementation outcomes [ 41 43 ]. All six interventions in the review reported high intervention acceptability.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We found several similarities when comparing our results to previous systematic reviews on implementation outcomes. Similar to previous reviews on implementation outcomes in LMICs, acceptability, appropriateness, and feasibility were the most frequently reported implementation outcomes [ 41 43 ]. All six interventions in the review reported high intervention acceptability.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, there was low reporting on intervention fidelity or descriptions on how the interventions are implemented which are crucial information for ensuring the successful replication or adoption of these interventions to maximize effectiveness and public health gains [ 55 ]. These gaps are in congruence with reviews of interventions in LMICs, which calls for more robust and consistent measurement of adoption [ 41 , 42 , 56 ] and fidelity [ 42 ]. Future reporting of mHealth interventions for young people in LMICs should consider providing detailed fidelity measures or information to provide structure for effective planning, implementation, and evaluation of interventions.…”
Section: Discussionmentioning
confidence: 55%
“…It is worth noting that every evaluation of effectiveness showed some treatment effect, typically with moderate to large effect sizes, for one or more CMDs [ 67 76 , 84 – 91 , 93 ]. Further, implementation research generally found lay-delivered talk therapies to be acceptable, appropriate and feasible to implement [ 77 – 89 , 92 , 93 ], echoing findings from a recent review of implementation outcomes of non-specialist-delivered CBT in LMICs (though the authors note the variable quality of this research) [ 106 ]. Several studies also demonstrated that with appropriate supervision systems in place, lay workers can deliver manualised talk therapies with a high degree of fidelity [ 84 88 ].…”
Section: Discussionmentioning
confidence: 80%
“…The implementation challenges for this cognitive-behavioral therapy group-based intervention are noteworthy. This intervention design, in consultation with the GHS, utilized peer mothers with low literacy in the local language and no formal health-care role to deliver the intervention as has been seen in other community-based mental health trials (Singla et al ., 2017; Verhey et al ., 2020). This strategy supported the potential sustainability of the intervention but came with literacy challenges for delivering the iMBC content with full fidelity.…”
Section: Discussionmentioning
confidence: 99%